(untitled) (Sound Stage Screen, 2023)
Introduction; Caroline Mounier-Vehier, Creating Opera for the Web: Au web ce soir – Ursule 1.1 and Actéon; Benjamin Lazar interviewed by Caroline Mounier-Vehier, Transposing the Necessity of the Present; Romeo Castellucci in conversation with Sofija Perović; Simon Hatab in conversation with Sofija Perovič; Julia Bullock in conversation with Sofija Perović.